2017
DOI: 10.1038/ijo.2017.12
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing study reveals common copy number variants in protocadherin genes associated with childhood obesity in Koreans

Abstract: Recently, the prevalence of childhood obesity has significantly increased in industrialized countries, including Korea, and now controlling obesity is becoming an economic burden. However, knowledge of the risk factors associated with obesity is still limited. In this study, we aimed to discover additional obesity-associated loci in children. To achieve this, we conducted an exome-wide association analysis of copy number variation (CNV) using whole-exome sequencing (WES) data from a total of 102 cases and 86 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Initially, we obtained information regarding MAF, chromosomal position, and alleles from approximately 22,000,000 variants of 2,576 sequenced Korean samples. These data consisted of 397 WGS from the Korean Reference Genome 37 and 2,179 WES encompassing 1,087 Korean samples from the T2D-GENES consortium 1 , 200 Korean samples from the Ansung and Ansan study 38 , 200 samples from a cardiovascular disease sequencing study 39 , and 692 samples from the Korean Children and Adolescents Obesity Cohort study 40 .…”
Section: Methodsmentioning
confidence: 99%
“…Initially, we obtained information regarding MAF, chromosomal position, and alleles from approximately 22,000,000 variants of 2,576 sequenced Korean samples. These data consisted of 397 WGS from the Korean Reference Genome 37 and 2,179 WES encompassing 1,087 Korean samples from the T2D-GENES consortium 1 , 200 Korean samples from the Ansung and Ansan study 38 , 200 samples from a cardiovascular disease sequencing study 39 , and 692 samples from the Korean Children and Adolescents Obesity Cohort study 40 .…”
Section: Methodsmentioning
confidence: 99%
“…However, in a study involving 30 extremely obese white adult subjects (mean BMI = 51.1 kg/m2), the detection of peripheral blood white blood cells showed that this rare mutation was significantly enriched, while this phenomenon was not found in the normal weight BMI population [32]. Rare mutations in the same gene were significantly enriched in another study involving obese Korean children [33]. When detected by urinary proteomic, the protein was detectable in the obese group with a mean BMI= 35.79 kg/m 2 which was significantly different from the normal weight group, side by side illustrating the sensitivity of urinary proteomics as well as demonstrating the potential of urinary proteomics in finding early markers of obesity.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with extreme obesity, cPcdhs have a significantly higher frequency of rare variants than in general population, indicating an association between rare variants of the Pcdh clusters and extreme obesity ( Table 1) (Mariman et al, 2014(Mariman et al, , 2015. In addition, copy number variations (CNVs) of two Pcdh genes, Pcdhβ7 and Pcdhβ8, are associated with increased body mass index (Moon et al, 2017). In mice, Pcdhγ regulates hypothalamic feeding circuitry (Su et al, 2010), which is known to be involved in extreme obesity.…”
Section: Clustered Pcdh Genes In Extreme Obesity With Behavioral Abnomentioning
confidence: 99%